Accumulation of assets in farms covered by the FADN farm accountancy system in Poland - the economic and eco-efficiency context = Akumulacja majątku w gospodarstwach rolnych objętych systemem rachunkowości rolnej FADN w Polsce - kontekst ekonomiczny i środowiskowy - Grzelak, Aleksander (Zielona Góra: Faculty of Economics and Management Press)
The primary objective of the article is to identify the accumulation processes in farms in Poland based on the economic size as well as the context of eco-efficiency (from the perspective of Environmental Sustainable Value). In addition, the importance of subsidies in generating accumulation was specified and the context of eco-efficiency was taken into account.
Keywords: akumulacja; gospodarstwo rolne; subsydia; ekoefektywność; dochody; accumulation; farm; subsidies; eco-efficiency; incomes